2003
DOI: 10.1093/nar/gkg330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stop codon readthrough genes in Saccharomyces cerevisiae

Abstract: We specifically sought genes within the yeast genome controlled by a non-conventional translation mechanism involving the stop codon. For this reason, we designed a computer program using the yeast database genomic regions, and seeking two adjacent open reading frames separated only by a unique stop codon (called SORFs). Among the 58 SORFs identified, eight displayed a stop codon bypass level ranging from 3 to 25%. For each of the eight sequences, we demonstrated the presence of a poly(A) mRNA. Using isogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 43 publications
6
115
0
Order By: Relevance
“…BSC4 has no significant homolog when we used tBLASTN to search against genome sequences of S. bayanus, S. kudriavzevii, S. mikatae, and S. paradoxus under the standard parameters. Even if we use the putative translation product of the stop codon bypass event predicted by Namy et al (2003), which is a peptide of 237 amino acids, there is still no significant homolog in these sibling species. The absence of homolog might be the false negative result due to incompleteness of the genomic databases of those species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BSC4 has no significant homolog when we used tBLASTN to search against genome sequences of S. bayanus, S. kudriavzevii, S. mikatae, and S. paradoxus under the standard parameters. Even if we use the putative translation product of the stop codon bypass event predicted by Namy et al (2003), which is a peptide of 237 amino acids, there is still no significant homolog in these sibling species. The absence of homolog might be the false negative result due to incompleteness of the genomic databases of those species.…”
Section: Resultsmentioning
confidence: 99%
“…This gene first caught our attention as a species-specific protein-coding gene in our genome comparison analysis among Saccharomyces species (H.-F. Jiang and W. Wang, unpublished data). Previously the BSC4 gene was found as one of the stop codon readthrough genes in baker's yeast by Namy et al (2003). They found that BSC4 has a typical readthrough nucleotide context around its stop codon and its readthrough frequency is 9% when cloned into a plasmid with reporter genes (Namy et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The eRF1, composed of three domains, functionally mimics a tRNA with the N-terminal domain recognizing the stop codon (Bertram et al 2000), the central domain with its methylated GGQ motif promotes hydrolysis of the peptidyl-tRNA bond (Heurgue-Hamard et al 2005), and the C-terminal domain interacts with eRF3. Recognition of all three stop codons by eRF1 is mediated by the YxCxxxF and TASNIKS motifs, as well as by other binding pockets/cavities in the N domain Namy et al 2001;Namy et al 2002;Namy et al 2003;Beznoskova et al 2015 Genes are grouped by publication/similar mechanism. Many examples given rely on a single publication and detailed mechanisms remain unknown.…”
Section: Termination and Recyclingmentioning
confidence: 99%
“…Previous studies indicated that the context in which a nonsense codon exists affects the efficiency with which it can be read through (Namy et al, 2003). …”
Section: Obtaining a [Psi + ]-Suppressible Allele In The Ura3 Genementioning
confidence: 99%